2015
DOI: 10.1093/bja/aev213
|View full text |Cite
|
Sign up to set email alerts
|

The Ageing Brain: Age-dependent changes in the electroencephalogram during propofol and sevoflurane general anaesthesia

Abstract: These profound age-related changes in the EEG are consistent with known neurobiological and neuroanatomical changes that occur during typical ageing. Commercial EEG-based depth-of-anaesthesia indices do not account for age and are therefore likely to be inaccurate in elderly patients. In contrast, monitoring the unprocessed EEG and its spectrogram can account for age and individual patient characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
274
1
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(313 citation statements)
references
References 63 publications
24
274
1
14
Order By: Relevance
“…Despite considerable progress in anesthesiology care and research, neural circuit mechanisms to explain MDDE-induced unconsciousness are yet to be defined. However, an emerging paradigm for probing anesthetic mechanisms is to study electroencephalogram (EEG) recordings and relate the findings to the behavioral state and putative neural circuit-level mechanisms (Ching et al, 2010, Cimenser et al, 2011, Supp et al, 2011, Purdon et al, 2013, Vijayan et al, 2013, Akeju et al, 2014a, Akeju et al, 2014b, Blain-Moraes et al, 2014, Akeju et al, 2015, Purdon et al, 2015a, Pavone et al, 2016). This approach is beginning to provide key insights into the mechanisms of anesthetic action.…”
Section: Introductionmentioning
confidence: 99%
“…Despite considerable progress in anesthesiology care and research, neural circuit mechanisms to explain MDDE-induced unconsciousness are yet to be defined. However, an emerging paradigm for probing anesthetic mechanisms is to study electroencephalogram (EEG) recordings and relate the findings to the behavioral state and putative neural circuit-level mechanisms (Ching et al, 2010, Cimenser et al, 2011, Supp et al, 2011, Purdon et al, 2013, Vijayan et al, 2013, Akeju et al, 2014a, Akeju et al, 2014b, Blain-Moraes et al, 2014, Akeju et al, 2015, Purdon et al, 2015a, Pavone et al, 2016). This approach is beginning to provide key insights into the mechanisms of anesthetic action.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies are dealing with intraoperative EEG dynamics and evaluation, paving the way to newer and more effective strategies. Such studies have recently shown a reduced alpha band power in elderly patients during unconsciousness as well as an elevated risk to develop burst suppression state during anesthesia [52]. This is crucial since avoidance of burst suppression states ( fig.…”
Section: Neuromonitoringmentioning
confidence: 99%
“…These indices have been designed with a one-size-fits-all approach in which the same index value is meant to represent the same state of unconsciousness, regardless of the anesthetic being administered, and without regard to significant age-dependent differences in anesthesia-induced electroencephalogram features. 24–26 Anesthesiologists have learned over the years that their use does not reduce the incidence of awareness 27 and that patients’ underlying brain states can vary substantially despite being maintained within the recommended index range. 26,28,29 Alternatively, the unprocessed electroencephalogram and its spectrogram make it possible to view directly the patient’s brain states under general anesthesia.…”
Section: In Replymentioning
confidence: 99%